PEMBERIAN PUPUK LIMBAH CAIR BIOGAS DAN UREA, TSP, KCl TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS(Zea mays saccharata Sturt.) - Fristy Novira; Husnayetti '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sweet corn is one of the crops that has a fairly large role in provide the nutritional needs of the people. One of the effort that can  be do to improve the growth and production of sweet corn is fertilization. Bioslurry can be used as an organic fertilizer to plants. Application of bioslurry is neeed to combine with an anorganic fertilizer that rich of elements such as  N P K  like Urea, TSP, KCl. This study aimed to know the effect of bioslurry and Urea, TSP, KClinteraction  on the growth and production of sweet corn (Zea mays saccharata Sturt.) and get the best gift. This research was experimently using a Randomized Block Design (RBD), which are arranged in factorial, which consists of 2 factors and 3 replications. Parameters measured were plant height (cm), number of leaves (pieces), male flowers appear time, female flowers appear time (HST), weigth of cob with husk per plot (gram), weigth of cob without husk per plot (gram ), cob length (cm) and cob diameter (cm). The results showing the interaction of fertilizer application bioslurry and Urea, TSP, KCl fertilizer were not significant on all parameters observation. Bioslurry application significantly affected the number of  leaves and female flowers appear time, while the application of  Urea, TSP, KCl significantly affected plant height. Application 2.25 liter bioslurry and Urea 175 kg / ha of + TSP 125 kg / ha + KCl 75 kg / ha gives the best results. Keywords: sweet corn, bioslurry, Urea, TSP, KCl fertilizer.